2020
DOI: 10.1016/j.ijfatigue.2020.105731
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure dependent fatigue life prediction for short fibers reinforced composites: Application to sheet molding compounds

Abstract: Because of the high variability of SMC microstructure due to material flow during thermoforming, fatigue life prediction in real automotive structure represents a huge challenge. In this paper, we present a two-step microstructure selection involving an original ultrasonic method which is briefly presented. Then, on the basis of four selected microstructure configurations, an accurate experimental damage analysis is performed including both monotonic and cyclic loading. The high microstructure dependence of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…From a microscopic point of view, strain-softening behavior is closely related to the initiation and propagation of micro-cracks in CFRP composites, and then it is manifested as material stiffness degradation on the macroscopic level. [40] Besides, the initiation of localized deformation, which usually occurs in the matrix or material interface, is caused on the material's microscale. The microscopic behavior is governed by the occurrence, growth, and interaction of cracks and voids, leading to eventual damage on the macroscale.…”
Section: Strain-softening Model Of Cfrpmentioning
confidence: 99%
See 3 more Smart Citations
“…From a microscopic point of view, strain-softening behavior is closely related to the initiation and propagation of micro-cracks in CFRP composites, and then it is manifested as material stiffness degradation on the macroscopic level. [40] Besides, the initiation of localized deformation, which usually occurs in the matrix or material interface, is caused on the material's microscale. The microscopic behavior is governed by the occurrence, growth, and interaction of cracks and voids, leading to eventual damage on the macroscale.…”
Section: Strain-softening Model Of Cfrpmentioning
confidence: 99%
“…To solve the problem that the progressive damage in the fiber direction (dominated by fiber failure) is difficult to be accurately simulated, the equivalent principle of strain dissipation energy proposed by Pfanner [38] is introduced in this work. [14,[38][39][40][41][42] The core of the equivalent principle of strain dissipation energy is that the damage state (residual stiffness and residual strength) is only dependent on the dissipated energy in the progressive damage process, while has nothing to do with the specific macroscopic loading history: quasi-static loading, high-speed loading or cyclic loading. Pfanner's theory has been successfully employed in fatigue research of composite, [39][40][41][42] but to the best of the our knowledge, it is the first time used in the quasistatic progressive failure analysis.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have been conducted concerning the mechanical behaviour of several SMC composites formulations [13,[21][22][23][24][25]. The focus has been on the multi-scale experimental analysis and modelling of the mechanical behaviour and damage of this class of composites materials [27,28]. It has been demonstrated that the non-linear behaviour of a standard SMC (such as the one in study) is mainly governed by fibre-matrix interface failure [21][22][23].…”
Section: Previous Workmentioning
confidence: 99%